2011
DOI: 10.1161/circheartfailure.110.960096
|View full text |Cite
|
Sign up to set email alerts
|

Increased 90-Day Mortality in Patients With Acute Heart Failure With Elevated Copeptin

Abstract: Background-In patients with heart failure (HF), increased arginine vasopressin concentrations are associated with more severe disease, making arginine vasopressin an attractive target for therapy. However, AVP is difficult to measure due to its in vitro instability and rapid clearance. Copeptin, the C-terminal segment of preprovasopressin, is a stable and reliable surrogate biomarker for serum arginine vasopressin concentrations. Methods and Results-The Biomarkers in Acute Heart Failure (BACH) trial was a 15-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(54 citation statements)
references
References 12 publications
4
50
0
Order By: Relevance
“…Further, multiple regression analysis showed NT-proBNP as an independent predictor of plasma copeptin level. These findings lend further support to previous studies suggesting AVP and copeptin as neurohormonal markers for HF (Schrier and Abraham 1999;Neuhold et al 2008;Alehagen et al 2011;Maisel et al 2011), similar to BNP and NT-pro-BNP. Copeptin is simultaneously released with AVP from the neurohypophysis in response to osmotic as well as nonosmotic stimuli.…”
Section: Discussionsupporting
confidence: 90%
“…Further, multiple regression analysis showed NT-proBNP as an independent predictor of plasma copeptin level. These findings lend further support to previous studies suggesting AVP and copeptin as neurohormonal markers for HF (Schrier and Abraham 1999;Neuhold et al 2008;Alehagen et al 2011;Maisel et al 2011), similar to BNP and NT-pro-BNP. Copeptin is simultaneously released with AVP from the neurohypophysis in response to osmotic as well as nonosmotic stimuli.…”
Section: Discussionsupporting
confidence: 90%
“…In patients with established coronary artery disease, copeptin was not a strong predictor of cardiovascular outcome 168 and is probably a better predictor in patients with heart failure than in patients with chest pain. 267 Measurement of BNP has been proposed as an early diagnostic test for patients presenting with chest pain. 44 Although studies have shown an additive value of simultaneous measurement of BNP and cardiac troponin, [268][269][270] increased sensitivity is achieved at the expense of diagnostic specificity.…”
Section: Role Of Neurohormonesmentioning
confidence: 99%
“…During hospitalization, natriuretic peptides are thought to be helpful in risk stratification,3, 4 and a fall in peptide levels correlate with a better prognosis 5, 6, 7, 8. Recently, other candidate peptides, such as mid‐regional pro‐adrenomedullin (MR‐proADM)2 and copeptin,9 were found to add prognostic value. Copeptin is C‐terminal fragment of pre‐pro‐vasopressin.…”
Section: Introductionmentioning
confidence: 99%